Crescimento, produtividade e nível crítico de fósforo para o quiabeiro em relação à adubação fosfatada - De Oliveira, Emídio C.A.; Da Silva, Gilmara P. [UNESP]; De Oliveira, Ruthanna I.; Filho, Moacyr Cunha; Lira, Mario A.; Freire, Fernando J. (Revista Brasileira de Ciencias Agrarias, 2013)
The study aimed to evaluate the growth, productivity attributes and soil P critical level, for okra cultivar, Clemson Spineless, regarding phosphorus fertilization at the seeding. The research was conducted under field conditions, in the Zona da Mata of Pernambuco state, Brazil. The experimental design was a randomized block with six replications. Treatments consisted of doses 0, 8, 16, 32, 65, 130 and 260 kg P2O5 ha-1. Was evaluated growth, fruit yield, number of fruits per plant and fruit weight. At the end of the growth cycle, was determined critical P level in soil. The plant height and stem diameter adjusted to the sigmoid model, with difference in phosphorus fertilization, in which it was found that application of 130 kg P 2O5 ha-1 provided greater plant growth, with values of 123.1 cm and 17.7 mm, respectively. The phosphorus provided increments in productivity attributes, being observed with the addition of 130 kg P 2O5 ha-1, gains of 3.44 Mg ha-1 of fruit, 3.33 fruits per plant. The P availability in soil increased with phosphate fertilization, which made it possible to determine the critical level in 79 mg dm-3.
Growth, yield and phosphorus critical level for okra in relation to phosphate fertilization
Keywords: Abelmoschus esculentus; Clemson Spineless; Phosphorus availability